2008
DOI: 10.1143/jjap.47.2060
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Carbon Nanotube Field-Effect Transistors with Local Electrolyte Gates

Abstract: We have fabricated local-electrolyte-gated carbon nanotube field-effect transistors (CNTFETs), in which the electrolyte functions as a local top gate. The local-electrolyte-gated CNTFETs in the electrolyte solution provided high performance in terms of subthreshold slope and transconductance, resulting from the modulation of the conduction in the carbon nanotube channel and the large gate capacitance. Using the local-electrolyte-gated CNTFETs, real-time protein detection based on the channel conductance modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…In this section, we describe CNTFETs with local electrolyte gates, in which switching occurs by the modulation of SWNT channel conductance. (17) We discuss the advantages and excellent properties of local-electrolyte-gated CNTFETs. The electrical properties of the local-electrolyte-gated CNTFETs in a solution were compared with those of back-gated CNTFETs in air.…”
Section: High-performance Cntfets With Local Electrolyte Gatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we describe CNTFETs with local electrolyte gates, in which switching occurs by the modulation of SWNT channel conductance. (17) We discuss the advantages and excellent properties of local-electrolyte-gated CNTFETs. The electrical properties of the local-electrolyte-gated CNTFETs in a solution were compared with those of back-gated CNTFETs in air.…”
Section: High-performance Cntfets With Local Electrolyte Gatesmentioning
confidence: 99%
“…Our initial study demonstrated the effectiveness of CNTFET sensors and their excellent electrical properties for the precise and highly sensitive detection of biomolecules in solution. (17) These properties of CNTFETs are suitable for the detection of various analytes. Therefore, two types of sensing using modifi ed CNTFET sensors are described next.…”
Section: Introductionmentioning
confidence: 99%
“…1 SWNTs are highly promising for the fabrication of nanoscale devices and microelectrodes. [2][3][4] In particular, SWNT structures are considered to be suitable channels of field-effect transistors ͑FETs͒, [5][6][7] which are expected to be used in single-electron transistors and highly sensitive biosensors. [8][9][10][11] In typical back-gated carbon nanotube FETs ͑CNTFETs͒, SWNT channels are exposed to the atmosphere, resulting in unstable electrical properties of CNTFETs.…”
Section: Electrical Characterization Of Carbon Nanotube Field-effect mentioning
confidence: 99%
“…(9)(10)(11) Biomolecules such as DNA and proteins were detected using CNTFETs. (12)(13)(14)(15)(16)(17)(18) CNTs are also reported to have a higher ability to promote electron transfer reactions than conventional metal electrodes for electrochemical measurements. (19) When CNTs have a high aspect ratio, the total surface area of working electrodes becomes larger when CNTs are modifi ed on the surface of electrodes.…”
Section: Introductionmentioning
confidence: 99%